Impact of Advertising Campaigns Among Online Gamblers: The Role Perceptions of Social Support and Personality Traits - Tessier, Samantha; Romo, Lucia; Zerhouni, Oulmann (Frontiers in Psychiatry, 2021)
Background: Few studies on problematic gamblers have focused on how environment and personality interact in gambling behavior. The aim of this research is to investigate how social support, dimensions of personality, and advertising campaigns are associated with gambling among problematic or moderate-risk gamblers and recreational gamblers and associated with online gambling (i.e., sport and poker). Methods: One hundred nine participants (45% problematic or moderate-risk gamblers) answered an online survey including social support, five factor models of personality, typology of gamblers, and several sociodemographic variables. Results: We found that problematic and moderate-risk gamblers were significantly more sensitive to gambling advertisements compared to light players. Social support was significantly lower among online gamblers compared to offline gamblers, but no association was found between social support and type of gamblers. Problematic and moderate-risk gamblers presented lower levels of extraversion compared with recreational gamblers. Notably, when the onset of gambling is before 18 years old, participants had more chances to recall more gambling advertisements as adults. Conclusion: We propose that future longitudinal research should focus on characteristics of online gamers particularly regarding social support to understand this low level of adequacy compared to offline gamblers.